Accurate gravity anomaly interpolation: a case-study in cameroon, central africa (2007)
Many treatments in geodesy and geophysics require regularly gridded gravity anomalies. The gridding of gravity data needs interpolation. For the predicted data to be accurate, the smoothest type ofgravity anomaly should be used along with the most indicated prediction method. This paper presents the comparison of various prediction methods applied on different types of gravity anomalies andconsidering the relative geological complexity of the study area. Many algorithms are tested and the suitability of each type of anomaly and each prediction method discussed in a case-study in Cameroon (Central Africa), using a set of 43,000 gravity data points to determine the must accurate prediction technique.